Hub Genes of Astrocyte Involved in Glaucoma with Ocular Hypertension by Integrated Bioinformatics Analysis - Yi-Jing YANG; Yu XIANG; Ye TIAN; Fei XIA; Ya-Sha ZHOU; Jun PENG; Qing-Hua PENG (KeAi Communications Co., Ltd., 2018)
ABSTRACT: Objective This study was conducted to elucidate the potential key candidate genes and pathways in role of astrocyte involved in glaucoma with ocular hypertension.Methods Expression profiles GSE2378 and GSE758 including 27 reactive optic nerve head astrocytes (ONHAs) by hypertensions and 26 normal controls, were integrated and deeply analyzed. Differentially expressed genes (DEGs) were sorted and candidate genes and pathways enrichment were analyzed. DEGs-associated protein-protein interaction network (PPI) was performed.Results A total of 119 consistently expressed genes were identified from 281 commonly changed DEGs, including 68 up-regulated genes and 51 down-regulated genes. PPI network complex filtered 75 DEGs (43 up-regulated and 32 down-regulated genes) of the 119 consistently altered DEGs and developed 117 edges, and 10 hub genes were identified. The most significant 3 modules were filtered from PPI, pathway enrichment analysis showed that module 1 was associated with extracellular exosome. Module 2 was mainly associated with antibody-dependent cellular cytotoxicity (ADCC) and module 3 was mainly associated with Hippo signaling pathway.Conclusion Taken above, using integrated bioinformatical analysis, we have identified DEGs candidate genes and pathways in role of astrocyte involved in glaucoma with ocular hypertension, which could improve our understanding of the cause and underlying molecular events, and these candidate genes and pathways could be therapeutic targets for glaucoma. Keywords: Glaucoma, Ocular hypertension, Reactive optic nerve head astrocytes, Hub gene, Pathway enrichment